Natural survivorship estimates for the West Coast rock lobster Jasus Lalandii obtained using a size-based modelling approach - Johnston, Susan Joy (Department of Biological Sciences, 2016)
Natural survivorship for the South African west coast rock lobster resource, Jasus lalandii, is estimated at two locations, Robben Island and Hout Bay. A size-based modelling approach is used, in which the model is fitted, to pristine catch size frequencies. The natural survivorship value for lobsters in the Robben Island region is estimated to be 0.94. The natural survivorship value for Hout Bay lobsters is estimated to be 0.87. The natural survivorship estimates are found to be very sensitive to rock lobster growth rate. The Robben Island estimate decreases from 0.968 for a decrease of 40% in the growth rate, to 0.9 7 for a increase of 40% in the growth rate. These estimates.are compared with those made for lobsters in more northern areas. The implications of these natural survivorship estimates are discussed. A simple, direct method is used to estimate natural survivorship for Robben Island and Hout Bay, and the results are compared to those obtained with the model. Includes bibliographical references (pages 64-68).